The Effects of Air Pollution on Respiratory Problems: A Literature Review - Krismanuel, Hari; Hairunisa, Nany (Poltekkes Kemenkes Palu, 2024)
As the global prevalence of air pollution continues to rise, understanding its intricate impact on human health, particularly respiratory well-being, becomes imperative. The research objectives of the article is to explore and establish clear connections between air pollution and respiratory health. Methods: A comprehensive search of peer-reviewed literature was conducted using databases such as PubMed, Web of Science, and Google Scholar. Articles published between 2015 and 2023 were included, with a focus on epidemiological studies, experimental research, and reviews that explored the impact of air pollution on respiratory problems. The result is this review synthesizes the established connections between these pollutants and a range of respiratory problems. Extensive evidence showcases how exposure to elevated pollutant levels escalates the risk of respiratory maladies, encompassing aggravated asthma, exacerbated chronic obstructive pulmonary disease (COPD) symptoms, compromised lung function, heightened susceptibility to respiratory infections, elevated lung cancer risk, and potentiated allergic responses. This review also underscores the heightened vulnerability of certain demographics, such as prenatal age, children, the elderly, individuals with preexisting respiratory conditions, low socioeconomic groups, occupational groups, outdoor workers, and athletes, immune-compromised individuals, and genetic susceptibility to these detrimental effects. The underlying mechanisms orchestrating the impact of air pollution on respiratory health involve intricate interplays of oxidative stress, inflammation, and tissue damage within the respiratory system. In conclusion: The study advocates for urgent and targeted strategies to mitigate the adverse impact of air pollution on respiratory health.